Recalibrating Christian Ethics at Corinth: Paul’s Use of Jesus the Prototype and Collective Remembrance to Provide Spiritual Guidance on Weaker Brothers and Food Offered to Idols - Williams, H. H. Drake (Religions, 2024)
Social identity theory has provided a fresh lens that can be used to look at Paul’s letters. Prototypes provide a helpful means to examine social identity and ethics in communities, as suggested by Warren Carter. In 1 Corinthians, Jesus Christ is presented as a prototype, although the Corinthians did not meet him. Collective memory theory has also provided a means to look at recollections of the person of Jesus recorded in the New Testament. While the number of recollections of Jesus that his recipients had is still open to question, this study finds Bauckham’s approach to the memory of Jesus in Paul to be the most sustainable. Studies by Dale Alison and Richard Burridge provide a general picture of ideas in the Synoptic tradition. When the fruits of prototype studies are combined with the collective memory of Jesus, it provides fresh insight into Paul’s commandment to imitate Jesus Christ, which was issued in 1 Cor 11:1. The fruits of these combined methods reveal the influence of the life of Jesus in the commands to look after the weak brother, abstain from idol feasts, and to do everything to God’s glory. Through the recollection of the lifestyle of Jesus, Paul recalibrates the Corinthian behavior so that it agrees with the prototype.